Comparison of the ultra-low-dose Veo algorithm with the gold standard filtered back projection for detecting pulmonary asbestos-related conditions: a clinical observational study. Issue 5 (30th May 2014) - Tekath, Marielle; Dutheil, Frédéric; Bellini, Romain; Roche, Antoine; Pereira, Bruno; Naughton, Geraldine; Chamoux, Alain; Michel, Jean-Luc
Abstract : Objectives: Radiation delivered during CT is a major concern, especially for individuals undergoing repeated screening. We aimed to compare a new ultra-low-dose algorithm called Veo with the gold standard filtered back projection (FBP) for detecting pulmonary asbestos-related conditions. Setting: University Hospital CHU G. Montpied, Clermont-Ferrand, France Participants: Asbestos-exposed workers were recruited following referral to screening for asbestos-related conditions. Two acquisitions were performed on a 64-slice CT: the gold standard FBP followed by Veo reconstruction. Outcome measures: Two radiologists independently assessed asbestos-related abnormalities, pulmonary nodules, radiation doses and image quality (noise). Results: We included 27 asbestos-exposed workers (63.3±6.5 years with 11.9±9.7 years of asbestos exposure). We observed 297 pleural plaques in 20 participants (74%). All patients (100%) had pulmonary nodules, totalling 167 nodules. Detection rates did not differ for pleural plaques ( Veo 87% vs FBP 97%, NS), pleural thickening (100% for both) and pulmonary nodules (80% for both). Interstitial abnormalities were depicted less frequently with Veo than FBP. False negative and false positive did not exceed 2.7%. Compared with FBP, Veo decreased the radiation dose up to 87% ( Veo 0.23±0.07 vs FBP 1.83±0.88 mSv, p<0.001). The objective image noise also decreased with Veo as much as 23% and signal-to-noise ratio increased up to 33%. Conclusions: A low-dose CT with Veo reconstruction substantially reduced radiation. Veo compared favourably with FBP in detecting pleural plaques, pleural thickening and pulmonary nodules. These results should be confirmed on a larger sample size before the use of Veo in clinical routine practice in asbestos-related conditions, especially regarding the low prevalence of interstitial abnormalities in this study. Trial registration number: NCT01955018.